Photofunctional Rare Earth Hybrid Materials - Yan, Bing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents the main research advances in the field of photofunctional rare earth hybrid materials. The first chapter discusses the fundamental principles, ranging from rare earth, rare earth luminescence, luminescent rare earth compounds and photofunctional rare earth hybrid materials. The main body of the book consists of six chapters exploring different kinds of photofunctional hybrid materials, such as hybrids based on organically modified silica; organically modified mesoporous silica; functionalized microporous zeolite and metal-organic frameworks; polymer or polymer/silica composite; and multi-component assembly of hybrids. It also includes a chapter introducing the photofunctional application of these hybrid materials. It is a valuable resource for a wide readership in various fields of rare earth chemistry, chemical science and materials science.
Keywords: Optical materials; Inorganic chemistry; Lasers; Nanochemistry; Optical Materials; Inorganic Chemistry; Laser; Nanochemistry